Novel transient cancellation control method for future generation of microprocessors - Kasparis, Takis; Abu-Qahouq, Jaber A.; Pongratananukul, Nattorn (My University, 2002)
Future on-board low-voltage, high-current dc-dc voltage regulator module (VRM) requirements for a new generation of microprocessors are increasingly becoming stricter than ever as the demand for high dynamic performance and high power density converters with very small and limited output voltage deviation continues to increase. Future VRMs may have to be proactive instead of reactive so that it can respond before the upcoming large load transients. A new method to limit the VRM output voltage variation under large load transients is proposed. This method to be known as Transient Cancellation Control will be presented in this paper and how it reduces the output voltage overshoot/undershoot.
Keywords: Microprocessors; Electromotive force; Voltage regulators